Multifunctional tools / Muhammad Syakir Mohd Ali, Ahmad Azizul Azman and Aliff Daniel Shamsul Baharin - Mohd Ali, Muhammad Syakir; Azman, Ahmad Azizul; Shamsul Baharin, Aliff Daniel (Faculty of Plantation and Agrotechnology, 2023)
Weeds are plants that grow in areas where they are not wanted. One of the biggest obstacles farmers around the world has to face is weed management (Korres et al., 2019). Weed can affect plant yield and growth due to competition between sunlight, water, and nutrient. For example, according to (Hasanuzzaman et al., 2021), in wheat field, a maize is seen as weed since it interferes the growth and development of wheat. Thus, any unwanted plants or weeds need to be removed before it affects the agriculture production. Moreover, drainage also plays an important role for agriculture production and environment (Castellano et al., 2019). Drainage is an artificial drain system created in every plantation to protect the crop from flood and overwatering. For example, when there is raining season, the crop without drainage will suffer and dead due to drowning with water and flood. However, crop with drainage will safe due to the water are being led to other location such as nearest river and pond. So, the drainage can prevent the plantation from flooding and save plant from drowning. This shows that, drainage is also contributing to agriculture environment and production. Now, the innovation created is multifunctional tools that can remove weed, improve drainage and plowing the soil. This innovation can contribute on reducing working time, helping farming activity to become easier and safe environment.